Los Fenómenos de la Interpretación musical. Un análisis consciente a los diferentes fenómenos musicales participantes en el proceso de intencionalidad de un intérprete. Aplicaciones en el repertorio pianístico. (2022)
Facing the field of research - creation, this work is born from "the set of diverse knowledge, in principle transdisciplinary” (Rincón, 2019). A common starting point in research works with this approach. Through psychological, ideological, semiologists and philosophers that respond to said transdisciplinarity propose investigations and results in need of an attitude of openness to joint work, to enable results that, although they start from different approaches, encompass aspects that they touch with life itself in its complexity (Rincón, 2019). Musical learning is involved in various phases, processes, paradigms, intentions and multiple interpretations that are rarely reflected upon. this in a moment determined led me to question myself in the face of a process, in which, although I was immersed, He didn't pay the required attention. At the same time, questions were raised regarding the practice on the piano The questioning formed investigatively huge questions that triggered the first starting point for this research: What is interpreting? Of course, the question itself is enormous and contains processes that would hardly be addressed in the present work. Even so, it works as an introduction to the research topic.And it is that, the approach to musical works fixes its attention on the visible phenomenon of music, being able to show how an interpreter executes a musical work seems to come to center the end of the musical process that complies with an industrialized mechanism that seeks to train certain number of years a musician suitable for the market, who can function in a industry and is suitable for production. The problem is that the process of understanding of the various phenomena that interact in musical performance does not respond to a pre-established scheme, but to the progress of each musician. Know the intent of each work allows the musician to feel comfortable at the time of a musical performance and happiness comfort allows the musician to become a participating agent of the musical interpretation, not just an executor. Such a reflection is taken from Favio Shifres, who, through a analysis of the performance of the same work by two pianists, reflects on the intervention of different agents that affect the interpretive results, showing that every interpretation and decoding of a score depends on these agents. Although there is some "guides" in the score that help determine the style and basis of the work (Shifres, 2001) the interpretive part comes from the consciousness of each interpreter (Lacárcel, 2003). The Phenomena of Musical Interpretation. 4 Nicolás Tejada Prieto – UAN music program This work takes Umberto Eco as its last pillar, who in his work “The limits of Interpretation” (1992) analyzes himself, restating four major problems of modern semiotics: i. the "Limits of interpretation", ii. the excessive waste of "energy interpretation", iii. "the criteria of economy of reading" and iv. a polemical attack on the "practice of deconstruction", thus trying to restore the balance between the "reader's intention" (Intentio Lectoris), "the intention of the author" (Intentio Auctoris) and "the intention in the text, regardless of the intentions of its author” (Intentio Operis) 1 (Eco, 1992.), at the time which shows that the principle of unlimited semiosis cannot consist in a derivation uncontrollable sense. (Echo, Umberto (1957). Taking these 3 pillars, it is intended to analyze three phenomena that in my opinion are part of interpretation: the phenomenon that I will call embodied technique, thamusical consciousness and structural decryption, in relation to the three intentions mentioned by Eco, reflecting on the role of the interpreter in phenomena interpretations other than visual, just as Shifres does, in a conscious and stable way. In this way it is intended to present everything in a final creative sample, my degree recital, where there will be elements perfected through this inner search, which will allow me discover myself and reach a state of calm that avoids the despair that I can reach feel as a performer when interpreting a piece.